2004
DOI: 10.1111/j.0030-1299.2004.13314.x
|View full text |Cite
|
Sign up to set email alerts
|

The number and size of seeds in common versus restricted woodland herbaceous species in central Iowa, USA

Abstract: Mabry, C. M. 2004. The number and size of seeds in common versus restricted woodland herbaceous species in central Iowa, USA. Á/ Oikos 107: 497 Á/504.Few plants have widespread distributions and occur wherever there is suitable habitat. Most species are absent from seemingly suitable sites because of limited colonizing ability. At a landscape scale colonization is limited by lack of seeds or suitable microsites, and this limit is likely to be exacerbated by current human alteration of the landscape. To test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 52 publications
(83 reference statements)
2
33
0
Order By: Relevance
“…Similarly, the association between undisturbed sites and basal phyllotaxy probably reflects the presence of ferns in these areas. The association between undisturbed sites, solitary flowers, and dehiscent fruits with 4-20 seeds suggests low reproductive output, which is consistent with other studies (Matlack, 1994;Dupré and Ehrlé n, 2002;Mabry, 2004). However, other traits that have also been associated with low dispersal capacity -lack of vegetative spread, few seeds/fruit, large seeds -were associated with disturbance for at least one of our two study areas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, the association between undisturbed sites and basal phyllotaxy probably reflects the presence of ferns in these areas. The association between undisturbed sites, solitary flowers, and dehiscent fruits with 4-20 seeds suggests low reproductive output, which is consistent with other studies (Matlack, 1994;Dupré and Ehrlé n, 2002;Mabry, 2004). However, other traits that have also been associated with low dispersal capacity -lack of vegetative spread, few seeds/fruit, large seeds -were associated with disturbance for at least one of our two study areas.…”
Section: Discussionsupporting
confidence: 91%
“…For example, a study in Iowa using taxonomically paired species showed that less common species had larger seeds than closely related common species (Mabry, 2004). However, without the paired design that allowed species' relatedness to be factored out, these patterns would not have been evident.…”
Section: Discussionmentioning
confidence: 99%
“…There was, however, no relationship between the dispersal capacity of species (as deduced from diaspore type and number) and their geographical range, which appears to be consistent with previous work (Eriksson & Jakobsson, 1998;Thompson et al, 1999;Jacquemyn et al, 2003), but contrary to findings of other studies (e.g. Eriksson & Jakobsson, 1998;Murray et al, 2002;Mabry, 2004). On the other hand, perennials with no or only limited clonal growth produced more diaspores per plant than strongly clonal species, which may confer a higher dispersal capacity.…”
Section: Abundancesupporting
confidence: 68%
“…Sowing and transplant experiments have also demonstrated that the absence of many species is caused by seed limitation (Eriksson & Ehrlen 1992; Turnbull et al . 2000; Mabry 2004). Thus, propagule availability has probably influenced the plant community in our farmed stands, even though the communities in logged stands show few long‐term effects on diversity (Pearson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, species with rapid clonal expansion and large numbers of seeds tend to be more frequent in altered stands (Eriksson 1995; Singleton et al . 2001; Mabry 2004). Stand age and distance from source habitat can interact with dispersal and further limit the colonization of altered stands (Matlack 1994).…”
Section: Introductionmentioning
confidence: 99%